Prevalence of prediabetes and type 2 diabetes in children with obesity and increased transaminases in European German‐speaking countries. Analysis of the APV initiative. Issue 4 (6th December 2019) - Koutny, Florian; Weghuber, Daniel; Bollow, E.; Greber‐Platzer, S.; Hartmann, K.; Körner, A.; Reinehr, T.; Roebl, M.; Simic‐Schleicher, G.; Wabitsch, M.; Widhalm, K.; Wiegand, S.; et al.
Summary: Background: Non‐alcoholic fatty liver disease (NAFLD), prediabetes and type 2 diabetes mellitus are known to be closely linked with obesity as early as during childhood. Objectives: The study aimed to determine the prevalence of prediabetes and T2DM in children with obesity with or without increased transaminases. Methods: Data from the observational multicentre ( n = 51), cross‐sectional Adipositas Patienten Verlaufsbeobachtung registry were analyzed. Mild increase (mild group) was defined by alanine transaminase (ALT) >24 to ≤50 U/L and moderate to severe increase (advanced group) by ALT > 50 U/L. Prediabetes and T2DM were defined according to recent IDF/ISPAD guidelines. Results: The prevalence of prediabetes and T2DM was 11.9% (95% CI: 11.0–12.8) and 1.4% (95% CI: 1.1–1.7) among all participants ( n = 4932; male = 2481; mean age 12.9 ± 2.7 years; BMI‐SDS 2.1 ± 0.5; Tanner stage 3.2 ± 1.5). The prevalence of impaired glucose metabolism (prediabetes and T2DM) was 13.8% (95% CI: 12.1–15.4) in the mild, 21.9% (95% CI: 18.8–25.1) in the advanced group, 10.7% (95% CI: 9.4–11.9) in the control group. Mild and advanced groups had greater odds ratios for prediabetes [1.42; 95% CI: 1.17–1.72, 2.26‐fold; (1.78–2.86), respectively], the advanced group also for T2DM [2.39 (1.36–4.21)] compared to controls. While an increase in transaminases predominantly affected boys, girls within the advanced group had a higher T2DM prevalence than males (5.4 vs. male 2.1%). Conclusions: Children with obesity and increased liver transaminases as surrogates of NAFLD should be screened for T2DM.